Visualization and interpretation of methane hydrate growth and dissociation in synthetic porous media - Flatlandsmo, Josef (The University of Bergen, 2015)
Sedimentary natural gas hydrates might play an important role in the future energy mix and the impact of methane release from natural gas hydrates can be significant also with respect to climate change. Vast amounts of methane gas are trapped in the subsurface permafrost and in submarine environments below sea floors. To understand the mechanisms of formation and dissociation on pore scale is fundamental to explain phenomena on core scale and making hydrate simulators on field scale. The three scales combined, will provide valuable data and understanding for field planning and testing. The experimental work presented in this thesis is visual observations conducted in a 2D silicon wafer micro-model with a one-to-one representation of the Berea sandstone pore network using a vertical pore depth of 25µm. In this thesis the overall objective was to characterize hydrate formation and dissociation on pore scale by direct visualization. The second objective was to identify the limiting factors for hydrate formation and growth in the micromodel and compare these to bulk properties. Hydrate formation attempts has been done both with vacuumed and non-vacuumed water. This to mimic the oxygen and nitrogen levels in reservoir and surface conditions respectively and tracing the three-phase-equilibrium line in both cases. No significant difference was found. Thin film interference was used to determine the thickness of the water and hydrate film. This turned out to be limited by wavelength of the visual light spectrum. Water films were found to be thinner than 140nm and the hydrate films to be thicker than 1500nm. The experimental setup was modified to enable live view monitoring of the micro-model and fluid flow through all four ports. A new cooling-chamber was constructed allowing a more efficient temperature control and quicker heating/cooling of the still water surrounding the micro-model. During fixed pressure and variable temperature experiments, it was found that even at conditions well within the hydrate equilibrium ...